Development of a BUMDesa Management Education Model to Increase the Economic Resilience of the Au Wula Village - Angge, Kandidatus; Pardiman, Pardiman; Farida, Eka (IKIP PGRI Bojonegoro, 2024)
The development of the BUMDesa Au Wula management education model must be carried out to produce better performance. Model development is carried out through the implementation of BUMDesa management and governance system education which leads to a digitalization system, especially in technical management of financial management and marketing of BUMDesa superior products. This research aims to develop and implement a BUMDesa management and governance education model including management, collaboration with other parties, and local economic development to increase the economic resilience of the community in Au Wula village. The research method used is research and development. The development plan is based on a model of increasing community economic resilience through BUMDesa management practices and the PIID-PEL program approach. The stages of the research consisted of pre-field, implementation, data analysis, data presentation, drawing conclusions, and checking the validity of the data. The results of the study show that the increase in the economic resilience of the people of Au Wula Village is the result of coaching and implementing: (1) General management elements at BUMDesa include planning, organizing, directing, coordinating and controlling; (2) Collaborative management with 60 farmers, additional workforce, transportation synergy, opening of vegetable markets, and scholarship programs from elementary schools to master's programs; (3) Development of the local economy through the establishment of ecotourism centers, MSME centers, and the involvement of youth groups.